2018
DOI: 10.1016/j.jconhyd.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Competitive transport processes of chloride, sodium, potassium, and ammonium in fen peat

Abstract: There is sparse information on reactive solute transport in peat; yet, with increasing development of peatland dominated landscapes, purposeful and accidental contaminant releases will occur, so it is important to assess their mobility. Previous experiments with peat have only evaluated single-component solutions, such that no information exists on solute transport of potentially competitively adsorbing ions to the peat matrix. Additionally, recent studies suggest chloride (Cl) might not be conservative in pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 74 publications
2
24
2
1
Order By: Relevance
“…The volumetric water content of the immobile region for all soil cores was 0.17 ± 0.07 cm 3 cm −3 ; this water fraction did not participate in the convective transport of chloride. The fractions of immobile water found in this study were lower than those found for pristine peat or less decomposed peat soils [18,33], but comparable to those of highly degraded peat soils and peat sand mixtures [13,28]. The amount of immobile water content is related to peat type, the stage of peat degradation, and boundary conditions [32,33].…”
Section: Non-equilibrium Flow and Transportcontrasting
confidence: 46%
See 1 more Smart Citation
“…The volumetric water content of the immobile region for all soil cores was 0.17 ± 0.07 cm 3 cm −3 ; this water fraction did not participate in the convective transport of chloride. The fractions of immobile water found in this study were lower than those found for pristine peat or less decomposed peat soils [18,33], but comparable to those of highly degraded peat soils and peat sand mixtures [13,28]. The amount of immobile water content is related to peat type, the stage of peat degradation, and boundary conditions [32,33].…”
Section: Non-equilibrium Flow and Transportcontrasting
confidence: 46%
“…In this study, the Peclet number of the mobile water region ranged from 2.8 to 4.5, indicating that advection processes dominated in the leaching tests [30]. The optimized β values of all soil cores ranged between 0.5 and 1 (Table 2), which can be taken as an indication that the investigated peat soils constituted a dual-porosity medium containing active and dead-end pores [31][32][33], where the active pores or mobile water region dominated the pore space of the four soil cores. The volumetric water content of the immobile region for all soil cores was 0.17 ± 0.07 cm 3 cm −3 ; this water fraction did not participate in the convective transport of chloride.…”
Section: Non-equilibrium Flow and Transportmentioning
confidence: 62%
“…Tracer techniques provide useful tools to explore water flow and solute transport processes in soils (Leibundgut, Maloszewski, & Kulls, ).Various forms of tracers such as isotope 18 O (Ronkanen & Kløve, ), salt (Baird & Gaffney, ; Hoag & Price, ; Liu et al, ; McCarter, Weber, & Price, ), fluorescence (Ramirez, Baird, & Coulthard, ) and dyes (Liu & Lennartz, ; Liu et al, ; Mooney, Holden, Ward, & Collins, ) have been applied onto peat in the field or laboratory. All tracer experiments verify that preferential flow is a common phenomenon in peat soils.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of solute transport properties and the identification of preferential flow also depend on the properties of applied tracers. Chloride as well as tritium tracers were retarded in less degraded peat soils (Liu et al, ; McCarter et al, ). The adsorption of chloride onto peat was found to be related to its concentration (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation